SERO-EPIDEMIOLOGY - S. Saiidi (Tehran University of Medical Sciences, 1973)
The term "serological epidemiology" is based to describe a method which has unique applications in comparing the immunologic status and health experiences of various populations, especially among populations for which morbidity data and vital statistics are scanty or completely lacking, or for inaccessible areas where the collection of serum is made with difficulty. Serologic and hematological surveys of diverse populations living in different environments have yielded information regarding the fields of epidemiology of infectious and non-infectious diseases, anthropology and genetics. Examples of the application of serological epidemiology to surveys of populations are given. Techniques and principles which are used in serological epidemiologic investigations are described, and the support of three so called W.H.O. Reference Serum Banks to expand the potentialities in this field is mentioned. Serum samples which are properly documented and stored can serve many purposes. Therefore, it is a timely and economic approach to do more cooperative and multipurpose research in epidemiology, both nationally and internationally.